Assalamualaikum, Rohingya!: Ini Kisah Travelog Kami Adalah Sebuah Misi - Nur Hanisah Zainoren,Dr., 1994-; Tuan Hissam Tuan Mamat; Wan Martina Wan Yusuff; Hafizul Husni Alias (Nur Hanisah Zainoren, 2018)
Includes bibliographical and references